What Is the Risk of Reactivation in Patients with Resolved and Past HBV Infection During Immunosuppressive Therapy If HBV-DNA Negative before Treatment? - Tokmak, Salih; Gümürdülü, Yüksel; Taş, Didem A.; Kara, İbrahim O.; Güzel, Ahmet B. (Turkish Journal of Gastroenterology, 2021)
Background: Reactivation of Hepatitis B (HBVr) related to immunosuppressive drug therapy (ISDT) in patients with resolved and pastinfection is a challenging entity. The number of prospective long-term studies is limited.Methods: Two groups of patients with resolved and past HBV infection were analyzed prospectively. The patients were further categorizedas 266 patients receiving ISDT (group 1) and 246 patients receiving antineoplastic therapy (group 2).Results: We did not detect any cases of HBVr among 108 patients receiving rituximab (71 of which were anti-HBc positive only),111 patients receiving tumor necrosis factor inhibitors (66 of which were anti-HBc positive only), and 42 patients receiving high-doseglucocorticoids for more than 4 weeks (24 of which were anti-HBc positive only) during a mean follow-up time of more than 24 months.Subgroup analysis of the anti-HBs (+) patients showed that in group A (anti-HBs >1000 mIU/mL) the antibody levels did not change; ingroup B (anti-HBs between 100 and 1000 mIU/mL) the antibody levels changed non-significantly (P = .25), and in Group C (anti-HBsbetween 0 and 100 mIU/mL) the antibody levels declined significantly (P = .002). Furthermore, 16 patients in Group C had an anti-HBsloss during follow-up, but no HBVr was detected.Conclusion: The risk of HBVr by immunosuppressive therapy in this group may be lower than that suspected in the literature and anti-HBs levels may not seem to correlate with the risk of reactivation.